Аналітичні дослідження енерговитрат пульсаційного гомогенізатора молока - Дейниченко, Г. В.; Самойчук, К. О.; Левченко, Л. В.; Deinychenko, G.; Samoichuk, K.; Levchenko, L. (My University, 2016)
UK: Досліджено вплив основних параметрів пульсаційного гомогенізатора: частоти та амплітуди руху поршня, діаметрів поршня та отворів у ньому, розмірів та маси поршня на енерговитрати пульсаційного апарата з одним поршнем. Отримано рівняння для визначення миттєвих та розрахункових значень для визначення потужності пульсаційного гомогенізатора. RU: Исследовано влияние основных параметров пульсационного гомогенизатора: частоты и амплитуды движения поршня, диаметров поршня и отверстий в нем, размеров и массы поршня на энергозатраты пульсационного аппарата с одним поршнем. Получены уравнения для определения мгновенных и расчетных значений для определения мощности пульсационного гомогенизатора. EN: The article contains analytical researches of one of the promising types of machines for fat emulsions and milk homogenization – pulsation homogenizer that has a piston with openings. This piston makes oscillation movement with the help of the crank gear in the cylindrical chamber. High efficiency of such homogenizer is conditioned by emulsion acceleration when the piston makes oscillation movement. Such movement increases emulsion dispersion level with the increase in slip velocity of the fat particle (globule) relatively milk plasma according to Veber's fracture criterion. Correlation of kinematic and design factors of the pulsation homogenizer with one piston with its energy consumption was not researched before. Thus, the aim of the article is to design mathematical apparatus in order to define energy consumption of the pulsation homogenizer of milk with one piston. The influence of basic parameters of pulsation homogenizer is investigated: frequencies and amplitudes of piston motion, diameters of piston and its openings, sizes and mass of piston on energy consumption of pulsation machine with one piston. The equations are received to determine instantaneous and calculation values for power determination of pulsation homogenizer. We analyzed the received curves of the three components of instantaneous power and also the total instantaneous power of the pulsation homogenizer depending on the oscillation frequency of the piston and average power of the pulsation homogenizer depending on the frequency and the pulsation amplitude. The largest contribution to total power belongs to the power on overcoming of inertia forces, and the smallest one belongs to the power for giving the energy to the liquid that pulsates in piston openings. The chart of total power is asymmetrical. Increase in the rotation frequency by 20–25% results in the increase of the power consumed by homogenizer more than twice. At n=3000 rpm and r=50 mm the power of homogenizer equals 3,5 kW. The suggested calculation procedure of energy consumption is recommended for use on the stage of the engineering design of the pulsation machine. It enables to define specific consumption of the homogenizer power and its efficiency compared to other equipment used for homogenization.
Аналитические исследования энергозатрат пульсационного гомогенизатора молока
Analytical researches of energy consumption of pulsation milk homogenizer
Keywords: гомогенізація; пульсаційний гомогенізатор; енерговитрати; аналітичні дослідження; гомогенизация; пульсационный гомогенизатор; энергозатраты; аналитические исследования; homogenization; pulsation homogenizer; energy consumption; analytical researches